2022
DOI: 10.1152/ajpcell.00258.2021
|View full text |Cite
|
Sign up to set email alerts
|

PDIA3/ERp57 promotes a matrix-rich secretome that stimulates fibroblast adhesion through CCN2

Abstract: The matricellular glycoprotein thrombospondin1 (TSP1) has complex roles in the extracellular matrix and at cell surfaces, but relatively little is known about its intracellular associations prior to secretion. To search for novel intracellular interactions of TSP1 in situ, we carried out a biotin ligase-based TSP1 interactome screen and identified protein disulphide isomerase A3 (PDIA3/ERp57) as a novel candidate binding protein. In validation, TSP1 and PDIA3 were established to bind in vitro and to colocalise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“…To further investigate the functional properties of CM, we investigated the role of heparin-binding proteins in the cell-spreading activity of CM from control MDA-MB-231 cells. Many secreted proteins that have roles in cell attachment and cell spreading contain heparin-binding domains ( 47 ), and we have shown that heparin-binding proteins are essential for the stimulation of spreading of Pdia3 −/− MEFs by CM from WT-MEFs ( 25 ). Serum-free CM was produced from control MDA-MB-231 cells as above and then mixed with either control agarose beads or heparin-agarose beads, the beads removed by centrifugation and filtration, and the residual supernatants tested in MDA-MB-231 cell spreading for 4 h. The CM depleted for heparin-binding proteins was markedly less effective at supporting MDA-MB-231 cell spreading assays and F-actin organization than the control CM or fresh FGM, as apparent from cell morphology ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To further investigate the functional properties of CM, we investigated the role of heparin-binding proteins in the cell-spreading activity of CM from control MDA-MB-231 cells. Many secreted proteins that have roles in cell attachment and cell spreading contain heparin-binding domains ( 47 ), and we have shown that heparin-binding proteins are essential for the stimulation of spreading of Pdia3 −/− MEFs by CM from WT-MEFs ( 25 ). Serum-free CM was produced from control MDA-MB-231 cells as above and then mixed with either control agarose beads or heparin-agarose beads, the beads removed by centrifugation and filtration, and the residual supernatants tested in MDA-MB-231 cell spreading for 4 h. The CM depleted for heparin-binding proteins was markedly less effective at supporting MDA-MB-231 cell spreading assays and F-actin organization than the control CM or fresh FGM, as apparent from cell morphology ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3 B , blue arrow). In addition, IGFBP7 is less abundant in the CM of Pdia3 -null MEFs compared with CM from WT-MEFs ( 25 ). IGFBP7 was detected principally in CM, with minor amounts in cell lysate, as a band of the expected molecular mass of 30 kDa.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations